Nonlinear optimum model following control of flexible aircraft. - André Luís da Silva (2010)
This Doctorate Thesis concerns optimum control of flexible aircraft. Models of a conceptual flexible aircraft are developed for control applications. A general model following problem via output feedback is developed and applied to the conceptual aircraft. The models are determined for 3 aircraft variants with increasing flexibility. The aerodynamics of flexible body is given by the Doublet Lattice method. The dynamics of the flexible structure is obtained via modal superposition. Controllability measures, given from control amplitude and rate constraints, are evaluated. Stabilization of flexible modes is performed via static output feedback. Control channels are defined with support of modal controllability and observability indexes. These applications contribute to determine the configuration of control surfaces. In order to treat the control of flexible aircraft, a rigid body approximation is proposed as the reference model. A general problem is posed, that consists in the determination of an optimum quadratic nonlinear output feedback for nonlinear plant and reference model, in order to approximate the input-output behavior of the reference model, for given performance outputs. Novel optimum and sub-optimum results, involving time variant and invariant linear state and output feedback and nonlinear time invariant output feedback, via neural networks, are developed. All these results are applied to the nonlinear model of conceptual aircraft and respective linear approximation, with comparisons among them. The efficiency and efficacy of the results are shown, and the importance of the nonlinear control is evidenced.